Effect of 1-pentanol addition and EGR on the combustion, performance and emission characteristic of a CRDI diesel engine. (January 2020) - Radheshyam; Santhosh, K.; Kumar, G.N.
Abstract: Experimental study of 1-pentanol addition and EGR rates on the combustion, performance and emission of a CRDI diesel engine is carried out in this work. 1-Pentanol being a higher alcohol has fuel properties comparable to diesel. Experiments were conducted on a 4 stroke two cylinder, CRDI diesel engine running at a constant speed of 2000 rpm for lower load and higher load. Test fuels were prepared by blending the 1-pentanol with diesel, and tests were carried out for 5%, 10%, 20%, 30% and 40%, 1-pentanol blended in diesel on a volume basis. Effect of EGR rates of 10% and 20% were also studied. It had observed that engine can be run up to 30% of 1-pentanol blended fuel without any engine modification, but with raise in the percentage of 1-pentanol in the blends, BSFC increases and BTE decreases. Combustion characteristic for blended fuel depends upon the load. At higher load due to premixed combustion MGT, CP and NHR were almost same compared to the diesel. Reduction in NOx emissions was noted for all the fuel blends at the cost of HC and CO emission. 1-pentanol is a renewable biofuel, with use of 1-pentanol the dependency on petrodiesel can be overcome. Highlights: 1-pentanol is a promising alternative to the diesel fuel. 1-pentanol blends reduce the CP, MGT and NHR at lower load and increases at higher load due to the premixed combustion. 1-pentanol blends and EGR reduce the BTE and increase the BSFC. Ignition delay period is increased for all the 1-pentanol blends due to low cetane number and EGR rate. 1-pentanol blends and EGR significantly reduces the NOx emission.